2020
DOI: 10.2147/pgpm.s247892
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of CYP3A5 Polymorphisms on Efficacy and Safety of Tacrolimus Therapy in Patients with Idiopathic Membranous Nephropathy</p>

Abstract: Background: Tacrolimus (TAC) is beneficial for patients with idiopathic membranous nephropathy (IMN). It has a narrow therapeutic concentration range and many factors influence TAC blood concentration. CYP3A5 is the most important enzyme in TAC metabolism. The aim of this study was to analyze the effects of CYP3A5 gene polymorphisms on the efficacy and safety of TAC in IMN patients. Patients and Methods: Patients with IMN who received oral TAC (0.05-0.075mg/kg/day) combined with prednisone (0.5mg/kg/day) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The observations among the different Sudanese ethnic groups tacrolimus trough concentrations were found to be variable, as Arabs and Fulani were observed to have low trough concentrations (n=6; 40%), while Nuba and Beja were observed to have high trough concentrations (n=5; 33.3%), instead of fur observed to had fluctuations (n=2; 13.3%). In many studies in literature the tacrolimus trough concentrations were found to had significant correlation with the CYP3A5 genotypes and tacrolimus level, CYP3A5(*1/1)/(*1/3) known as expressor, indicated high dose required to obtained the target level, and CYP3A5 (*3/3) non-expressor therefore, low dose required for those category of patients to prevent toxicity (20,25,26). No study was done yet to detect the genotypes of the Sudanese population of kidney transplants, these results could be confirmed when the genotype alleles investigate.…”
Section: Table (1): Areas Of Currently Practicing Doctor Specialty Ye...mentioning
confidence: 99%
“…The observations among the different Sudanese ethnic groups tacrolimus trough concentrations were found to be variable, as Arabs and Fulani were observed to have low trough concentrations (n=6; 40%), while Nuba and Beja were observed to have high trough concentrations (n=5; 33.3%), instead of fur observed to had fluctuations (n=2; 13.3%). In many studies in literature the tacrolimus trough concentrations were found to had significant correlation with the CYP3A5 genotypes and tacrolimus level, CYP3A5(*1/1)/(*1/3) known as expressor, indicated high dose required to obtained the target level, and CYP3A5 (*3/3) non-expressor therefore, low dose required for those category of patients to prevent toxicity (20,25,26). No study was done yet to detect the genotypes of the Sudanese population of kidney transplants, these results could be confirmed when the genotype alleles investigate.…”
Section: Table (1): Areas Of Currently Practicing Doctor Specialty Ye...mentioning
confidence: 99%
“…Then, two studies with no available data on reported outcomes and four studies without concerning outcomes were excluded. As a result, eight studies involving 498 Chinese membranous nephropathy patients were finally included through screening (Ye et al, 2014;Yang et al, 2015;Wei et al, 2018;Lin et al, 2019a;Wu, 2019;Wang, 2020;Zhang et al, 2020;Xu et al, 2021). The course of study selection is given in Figure 1.…”
Section: Study Inclusionmentioning
confidence: 99%
“…A total of seven studies (Yang et al, 2015;Wei et al, 2018;Lin et al, 2019a;Wu, 2019;Wang, 2020;Zhang et al, 2020;Xu et al, 2021) reported the relationship between the AA + AG genotype (referred to as expressers) and the GG genotype (referred to as non-expressers) TAC blood trough concentrations in CYP3A5*3 genotypes. As the different durations of drug administration may have an impact on the pharmacokinetics and pharmacodynamics of TAC, the studies were divided into subgroups for analysis, according to the duration of TAC administration: ≤1 month, 1-6 months, and ≥6 months.…”
Section: Relationship Between Cyp3a5*3 Genotype Polymorphisms and Tac...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, paucity of information about the underlying molecular mechanisms in tandem with meager data is an obstacle to conclude the risks associated with adverse effects of this drug in case of prolonged course of treatment. [3][4][5][6][7] Immunosuppressive drugs may also have off target effects due to impaired mitochondrial and T-cell functions which lead to production of reactive oxygen species and induction of apoptotic cell death. 8 Patients undergoing immunosuppressive therapy after organ transplantation often display obesity and hyperlipidemia owing to accumulation of triglycerides in liver, therefore, liver targeted management should be taken into account to avoid liver complications.…”
Section: Introductionmentioning
confidence: 99%